Indian Muslims in Malaysia: a sociological analysis of a minority ethnic group - Muhamad Shukri, Abdul Salam; Abdullah @ Chuah Hock Leng, Osman; Yeoh, Mohd Syukri (Routledge Taylor & Francis Group, 2011)
This article analyses the status of Indian Muslims in Malaysia from a historical perspective and its definition as a minority ethnic group. It also highlights the political reality of the Indian Muslims, particularly as a smaller and relatively insignificant minority group in comparison with the numerically larger Malays as well as the non-Muslim Chinese and Hindu Indians. It describes the social interactions of the various ethnic groups in Malaysia and the Indian Muslims as a minority fighting for their identity and survival. It discusses the “position” of the Indian Muslims with particular reference to Article 152 of the Malaysian Constitution which states that a Malay person is defined as one speaking the Malay language, practicing Malay customs, and following the religion of Islam. The great contributions of Indian Muslims are also elaborated. This inquiry highlights the reality facing the Indian Muslims in Malaysia today: they have no political power but remain a marginalized minority in the midst of Malay political domination and Chinese economic hegemony. Indeed they are facing the grim prospect of permanent bifurcation of their identity—some are slowly but surely being assimilated into the Malay cultural milieu, mainly through marriage and for political expediency, on the one hand and others stubbornly resist this cultural absorption, and resiliently retain and preserve their ethnic traditions and purity.